PENERIMAAN PAJAK PENGHASILAN PRIBADI SEBELUM DAN SESUDAH DIBERLAKUKANNYA TARIF PAJAK PENGHASILAN TAHUN 2000 - Eka Adiputra (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
Tax represents the source of state acceptance which play important role in sustaining the development. Economic crisis in 1998 years making growth of Indonesia economics lost ground. This matter also affect at acceptance of tax, one of them acceptance of Personal Income Tax in Surabaya. Acceptance Of Personal Income Tax continue to experience of degradation. This matter push to releasing of new invitation to correspond to the condition of economics at that moment, that is with change of tax rate Income Tax in 2000 years. Change of income tax rate in 2000 years expected can improve acceptance of Income Tax specially Personal Income Tax. Methods used in this study is qualitative research method. Research aims to analysis affect of new tax rate.